2018
DOI: 10.1053/j.gastro.2018.06.082
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal and Extra-Intestinal Manifestations of IgG4–Related Disease

Abstract: IgG4-related disease (IgG4-RD) is a chronic relapsing multi-organ fibro-inflammatory syndrome of presumed autoimmune etiology. It is characterized by increased serum levels of IgG4 and tissue infiltration by IgG4 cells. Increased titers of autoantibodies against a spectrum of self-antigens and response to steroids have led to its characterization as an autoimmune disease. However, the pathognomonic antigens probably differ among manifestations, and different antigens or autoantibodies produce similar immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 102 publications
(127 reference statements)
0
48
0
6
Order By: Relevance
“…However, the cut-off points vary depending on organ system. Some studies have suggested that IgG4 + /IgG + plasma cell ratio > 0.4 is a marker of IgG4-RD in the presence of classic histopathological features and with a compatible clinical features [1,17].…”
Section: Discussionmentioning
confidence: 99%
“…However, the cut-off points vary depending on organ system. Some studies have suggested that IgG4 + /IgG + plasma cell ratio > 0.4 is a marker of IgG4-RD in the presence of classic histopathological features and with a compatible clinical features [1,17].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wallace et al analyzed 765 patients and could identify 4 different phenotypes of IgG4-RD (pancreato-hepato-biliary disease, retroperitoneal fibrosis and/or aortitis, head and necklimited disease, and classic Mikulicz syndrome with systemic involvement) [28]. Abdominal IgG4-RD mostly affects the pancreas, the bile ducts, and the retroperitoneum and represents the first 2 phenotype groups [1,28]. In contrast, gastric IgG4-RD is rare.…”
Section: Discussionmentioning
confidence: 99%
“…IgG4-RD mostly affects the pancreas, bile ducts, salivary and lacrimal glands, kidneys, retroperitoneum, mediastinum, and lung. Virtually any organ can be involved, and multiorgan involvement is common [1]. An infiltration of IgG4-positive plasma cells in the gastric tissue of patients with autoimmune pancreatitis (AIP) has been reported [2].…”
Section: Introductionmentioning
confidence: 99%
“…IgG4-related sclerosing cholangitis is a rare disease and has a high degree of clinical and radiologic resemblance to cholangiocellular carcinoma. 1 It is important to differentiate it from malignant diseases, because IgG4-related sclerosing cholangitis can respond to steroid treatment with a better prognosis. The diagnosis of IgG4-related cholangitis usually needs serum IgG4 measurement as well as histologic analysis.…”
mentioning
confidence: 99%
“…A ratio of IgG4/IgG cells of >40% is helpful to discriminate it from other disorders. 1 However, to establish the diagnosis, another histologic feature, such as storiform fibrosis, lymphoplasmacytic infiltration, or obliterative phlebitis, is necessary.…”
mentioning
confidence: 99%